Defining Strategies for Novel Snowboard Design - Subic, A.; Clifton, P.; Beneyto-Ferre, J. (The Engineering of sport 7, Volume 1, 2008)
There is considerable anecdotal evidence that suggests snowboarders relate the perceived "feel" of a snowboard to its on-snow performance. The Snowboard Research Group at RMIT University in Melbourne thus set out to fully characterise the "feel" of snow-boards for the main riding styles. By correlating subjective evaluations to objective laboratory and field based data, the relevant matrices of parameters leading to the desired "feel" of the board can be determined. This article deals with the front-end of the characterisation process by focusing on the Identification of potential design innovation opportunities through a benchmarking analysis of modern snowboards.